Building a hospital‐based addiction medicine consultation service in Vancouver, Canada: the path taken and lessons learned. (27th January 2021) - Braithwaite, Vivian; Ti, Lianping; Fairbairn, Nadia; Ahamad, Keith; McLean, Mark; Harrison, Scott; Wood, Evan; Nolan, Seonaid
Abstract: Background and aims: To improve evidence‐based addiction care in acute care settings, many hospitals across North America are developing an inpatient addiction medicine consultation service (AMCS). St Paul's Hospital in Vancouver, Canada houses a large interdisciplinary AMCS. This study aimed to: (1) describe the current model of clinical care and its evolution over time; (2) evaluate requests for an AMCS consultation over time; (3) highlight the established clinical training opportunities and educational curriculum and (4) provide some lessons learned. Design, setting and participants: A retrospective observational analysis in an urban, academic hospital in Vancouver, Canada with a large interdisciplinary AMCS, studied from 2013 to 2018, among individuals who presented to hospital and had a substance use disorder. Measurements: Data were collected using the hospital's electronic medical records. The primary outcome was number of AMCS consultations over time. Findings: In 2014 the hospital's AMCS was restructured into an academic, interdisciplinary consultation service. A 228% increase in the number of consultations was observed between 2013 (1 year prior to restructuring) and 2018 (1373 versus 4507, respectively; P  = 0.027). More than half of AMCS consultations originated from the emergency department, with this number increasing over time (55% in 2013 versus 74% in 2018). Referred patients were predominantly male (> 60% in all 5 years) between the ages of 45 and 65 years. Reasons for consultation remained consistent and included: opioids (33%), stimulants (30%), alcohol (23%) and cannabis use (8%). Conclusions: After St Paul's Hospital in Vancouver, Canada was restructured in 2014 to a large, interdisciplinary addiction medicine consultation service (AMCS), the AMCS saw a 228% increase in the number of consultation requests with more than half of requests originating from the emergency department. Approximately two‐thirds of consultation requests were for opioid or stimulant use.